A new Aphidius Nees (Hymenoptera, Braconidae, Aphidiinae) of Ericaphis fimbriata (Richards) (Hemiptera, Aphididae) and key to parasitoids of blueberry aphid in the Pacific Northwest - Pike, Keith S.; Starý, Petr; Graf, George; Raworth, David A.; Mathur, Sneh; Tanigoshi, Lynell K.; Murray, Todd (Zootaxa, 2011)
Aphidius ericaphidis Pike & Starý, sp. nov., is described and illustrated. This aphidiine is a parasitoid of the blueberry aphid, Ericaphis fimbriata (Richards), widely found associated with the commercial highbush blueberries, Vaccinium corymbosum L., in southwestern British Columbia, Washington, and in northeastern Oregon. It is one of several species of aphidiines known to attack E. fimbriata in North America. A key is provided to distinguish it from other parasitoid species of E. fimbriata.